Application of student-centred learning principles to mixed-mode delivery : an investigation of theory, practice and impact on the quality of learning and teaching - Kennedy, Chona Pineda (Curtin University, 2013)
This study examines how closely aligned the teaching and learning practices, in selected mixed-mode programmes are with a student-centred approach as well as the impact of the practices on the quality of learning and teaching in a New Zealand Māori institution.Using a sequential, mixed-methods research approach, a survey was conducted in class followed by one-to-one interviews with the tutors and students in the sample to gather their perceptions and views regarding learning and teaching practices.